PENGARUH KOMPETENSI, SISTEM PENGENDALIAN INTERNAL, DAN KUALITAS PENYAJIAN LAPORAN KEUANGAN TERHADAP AKUNTABILITAS PEMERINTAH DESA - Sweetenia, Amanda Mutiara; Caesari, Eka Pinditya Ayu; Aprillia, Arum Frida; Purwantini, Anissa Hakim (Universitas Muhammadiyah Magelang, 2019)
This study empirically investigates the factors that influences accountability of village governments in managing the Allocation of Village Funds in terms of Competency of the village apparatus, Internal Control System, Quality of presentation of financial statements. The sampling technique used in this research is purposive sampling, which is the official of the local government budget team in each sub-district within the scope of Magelang Regency. Based on survey responses from 150 respondents, the results show that Internal Control System and the quality of presentation of financial statements affect the accountability of management of ADD in Magelang regency. Meanwhile, competency has no effects on the accountability of managing the the Allocation of Village Funds.